Custo de produção e lucratividade da cultura do amendoim no município de Jaboticabal, São Paulo - Barbosa, Rafael Marani [UNESP]; Homem, Bruno Fernandes Modesto [UNESP]; Tarsitano, Maria Aparecida Anselmo [UNESP] (Universidade Federal de Viçosa, 2014)
The region of Ribeirão Preto in the State of São Paulo is the largest peanut producer in Brazil, where the crop is cultivated in leased areas in succession and rotation systems, mainly for renewal of sugarcane plantations. In this case, the rotation with peanut during the fallow period is a viable alternatve because is profitable and keep the areas productive. Thus, the aim of this study was to estimate and analyze the production cosst and profitability of peanut cv. Runner IAC 886 in the renewal of sugarcane areas in Jaboticabal, São Paulo, for the crop year 2010/2011. The methodology of Total Operating Cost was applied along with the profitability indicators: gross revenue, operating income and profitability index, considering three levels of prices received by producers. The total operating cost of peanut production was R $ 3,665.21 ha-1, mainly due to expenditure on crop and land lease. Economic indices were satisfactory only for the price level represented by the mean value obtained in recent years. Results failed to show profit for the Minimum Price Guarantee.

O Estado de São Paulo é o maior produtor de amendoim do Brasil e a produção concentra-se na região de Ribeirão Preto, onde o cultivo é realizado em áreas arrendadas, em esquemas de sucessão e rotação, principalmente, para reforma de canaviais. Nesse caso, a rotação com amendoim durante a entressafra é escolha viável, pois além de poder ser rentável, as terras que ficariam ociosas mantêm a sua produtividade. Por esta razão, o objetivo deste trabalho foi estimar e analisar o custo de produção e a rentabilidade do amendoim cv. Runner IAC 886, em áreas de reforma de canaviais, na região de Jaboticabal, São Paulo, para a safra 2010/2011. Utilizou-se a metodologia do Custo Operacional Total e calcularam-se os indicadores de lucratividade: receita bruta, lucro operacional e índice de lucratividade, considerando-se três níveis de preços recebidos pelos produtores. O custo operacional total da produção de amendoim foi de R$3.665,21 ha-1, devido, principalmente, às despesas com colheita e arrendamento da terra. Os índices econômicos foram satisfatórios somente para o nível de preço representado pelo valor médio obtido nos últimos anos. Em relação ao Preço Mínimo de Garantia, os resultados não apresentaram lucro.
Production costs and profitability of peanut in Jaboticabal, São Paulo
Keywords: Arachis hypogaea L.; reforma de canavial; rentabilidade; rotação; Arachis hypogaea L.; profitability; sugarcane renewal; rotation